Reformulating Defamation Offenses: Implications for Freedom of Expression in Indonesia’s Digital Space - Rahman, Arif; Hamim, Sufian; Admiral, Admiral; Susanti, Heni (UIR Press, 2026)
Freedom of expression in the digital space constitutes a fundamental democratic right; however, its exercise in Indonesia has increasingly been constrained by the criminalization of online speech through defamation provisions. This article examines the reformulation of defamation and libel offenses under Indonesia’s New National Criminal Code (KUHP) and assesses its implications for freedom of expression and digital democracy. Employing a normative legal research method, the study analyzes the normative shift from the Information and Electronic Transactions Law (ITE Law) to the KUHP, with particular attention to the recalibration of criminal boundaries and the classification of defamation as a complaint-based offense. The findings indicate that the reform represents an attempt to reduce over-criminalization and mitigate the “chilling effect” on public discourse by strengthening procedural safeguards and limiting state intervention. Nevertheless, ambiguities in interpretation and the absence of detailed enforcement guidelines may still expose individuals to legal uncertainty, particularly in cases involving criticism of public officials and governmental institutions. This article argues that, despite progressive intent, the reconfiguration of defamation offenses requires careful judicial interpretation and proportional enforcement to prevent the persistence of restrictive practices in digital communication. The study contributes to ongoing debates on the balance between protecting reputation and safeguarding freedom of expression in the context of Indonesia’s evolving criminal law framework.